Higher education for public value: taking the debate beyond New Public Management. Issue 2 (23rd February 2018) - Broucker, Bruno; De Wit, Kurt; Verhoeven, Jef C.
ABSTRACT: Many higher education (HE) system reforms in the past decades have been built on the paradigm of New Public Management (NPM). However, these reforms have not allowed HE to fully take its value for society into account. In recent years a growing call can be heard to orient the HE sector towards more collaboration, a focus on a larger set of socio-economic objectives instead of on performance alone, less pressure, more trust and legitimacy. In this article, it is stated that NPM has not sufficiently enabled the creation of public value (PV) by the HE sector. This article provides (1) insight into the flaws of NPM, (2) an understanding of PV for HE and (3) a new model to study HE reforms built on the concept of PV.